2018
DOI: 10.1101/481424
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-throughput genotyping of the spelt gene pool reveals patterns of agricultural history in Europe

Abstract: Spelt, a close relative of hexaploid bread wheat and a dominant wheat subspecies cultivated in Europe before the 20 th century, still plays an important role as a high-value niche product today.Compared to most other cereals, spelt has not been subjected to intensive breeding in the 20 th century. Even today, mostly traditional landraces are cultivated on a regional scale. The traditional way of spelt cultivation has limited the extensive exchange of germ plasm and intermixing of genetic material, which makes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The discrepancy of the archaeological record where bread wheat was ahead of spelt wheat (Nesbitt and Samuel, 1996) would also be explained by this concept. Recently, Abrouk et al (2018) reported the European spelt markedly differed from Asian spelt/bread wheat and various reports suggested the European spelt wheat diverged from bread wheat by hybridization with tetraploid emmer wheat (Blatter et al, 2002(Blatter et al, , 2004. Several morphological and molecular studies also suggested the polyphyletic nature of European and Asian spelt wheat (Dvorak et al, 2012).…”
Section: Triticum Species Discriminationmentioning
confidence: 99%
“…The discrepancy of the archaeological record where bread wheat was ahead of spelt wheat (Nesbitt and Samuel, 1996) would also be explained by this concept. Recently, Abrouk et al (2018) reported the European spelt markedly differed from Asian spelt/bread wheat and various reports suggested the European spelt wheat diverged from bread wheat by hybridization with tetraploid emmer wheat (Blatter et al, 2002(Blatter et al, , 2004. Several morphological and molecular studies also suggested the polyphyletic nature of European and Asian spelt wheat (Dvorak et al, 2012).…”
Section: Triticum Species Discriminationmentioning
confidence: 99%
“…Recent advancements in genomics (e.g., genotype by sequencing, see below) have enabled exploration of this genetic diversity, leading to the discovery of markers and associated quantitative trait loci (QTLs) that can be utilized in marker assisted selection and genomic selection to accelerate variety development (Huang and Han, 2014). Wheat has a large and complex genome (Marcussen et al, 2014;Shi and Ling, 2017;Uauy, 2017;Abrouk et al, 2018). Very recently, however, an annotated reference whole genome sequence for bread wheat was released, which described 107,891 high-confidence level genes (IWGSC, 2018).…”
Section: Introductionmentioning
confidence: 99%